Marketing Management of Boarding School in Increasing Community Interest - Fauziyatul Iffah; Yayuk Fauziyah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Seeing the phenomenon of competition between Islamic boarding schools with one another, it is hoped that Islamic boarding schools will be smart in competing, namely by applying marketing management in it, so that the community as consumers feel satisfied with Islamic boarding school education services. The role of management here is very much needed to develop pesantren, especially marketing management. This research is qualitative with phenomenology, to describe the paradigm of reality. The marketing management of the Qowiyyul Ulum and Ulul Albab Islamic boarding schools which is the focus of the researcher refers to Kotler's theory and is strengthened by Muhaimin which includes planning, implementation, and supervision. Both are have similarities and differences in implementing marketing management for pesantren education. The effectiveness of marketing management does not depend on the length of the pesantren's establishment. However, this depends on the management carried out on the marketing of Islamic boarding school education. In this case, the marketing management of Ulul Albab Islamic boarding school education is more effective than Qowiyyul Ulum, as evidenced by the increase in the number of new students per year, Ulul Albab students increase by approximately 50% to 65% per year. years, while the Qowiyul Ulum students increase by about 20% to 25% per year.